IMPLEMENTASI BALANCED SCORECARD SEBAGAI ALAT PENGUKUR KINERJA PADA RUMAH SAKIT BHAYANGKARA POLDA BENGKULU - Sibarani, Antoni; Zahara, Nani Halima (JURNAL EKOMBIS REVIEW, 2014)
Antoni Sibarani, Nani Halima Zahara; The Implemetation of Balanced Scorecard as a tool of measuring performance in Bayangkara Polda Hospital of Bengkulu. This research aims to determine how the performance of Hospital by using the ?Balanced Scorecard?. The use of ?Balanced Scorecard? is expected that hospital can improve/develop the financial and non-financial performances for measuring the evaluation activity, so it will provide the satisfication to the customers, employers, and also sufficient surplus. This study took the data within the lastest two years (2011 to 2012) by using a comparative analysis, the researcher evaluated the performances of hospital between several periods and then compare with the pervious targets which have been set and scored according to the criteria. The data obstained from some sources; the evaluations of Hospital Bhayangkara within four perspectives; financial, customers, internal bussiness processes, and learning and growth . From the results of the study the concept of the Balanced Scorecard measurement can be deduced from the overall performance of Bhayangkara Hospital Bengkulu is 0.57. This study showed that Hospital Bhayangkara getting better if it is measured with the Balanced Scorecard approach.